Verbale Aggression: das Spektrum der Funktionen - Havryliv, Oksana (Linguistik Online, 2017)
Although verbal aggression plays an important role in people’s lives, this subject has been tabood for a long time in both public and in scientific terms. However, an interest in this topic has increased in recent years, especially from the perspective of language as a means of violence. Characteristically the study of language as a means of violence is pursued not as primarily linguistic one, but from the perspective of philosophy of language, and the terms verbal aggression and verbal violence are regarded as synonyms. In this article we will draw a line between these two terms and present the results of our surveys and case studies suggesting that verbal aggression is a complex linguistic phenomenon. Departing from our observations we will try to show that both the intention aimed at humiliation of the addressee (when verbal aggression equals to verbal violence), as well as intentions that are not aimed at verbal violence and that we can call efficient may be false, since the need to communicate negative emotions is inherent in people’s communication (emotional function of language), aimed at expressing some negative moments, rather than intending to offend the addressee. These productive functions of verbal aggression, which are emphasized in the field of psychology, have not been sufficiently studied from linguistic perspective. Special attention in the article is given to the relation of verbal and physical aggression. The article is illustrated by the examples from the German language (on the ground of our empirical data, based on oral and written surveys of the residents of Vienna - 700).